Chemical modifications of boron nitride nanotubes with heterocyclic molecules: A DFT study - Abdelmajeed Adam Lagum; Wathiq Kh. Mohammed; Eyhab Ali; Sahar balkit hussein; Usama S. Altimari; Ashwaq Talib Kareem; Ali Alsalamy; Ameer S. Alkhayyat; Hashem Al-Shaaban (Chemical Physics Impact, 2023)
The density functionals M06–2X and B3LYP were exploited for investigating the impact of modifying the surface of a boron nitride nano-tube (BNNT) with the furan molecule in terms of energy, electronics, and geometry. According to the density functional theory (DFT) results, BNNT had a strong interaction with the furan molecule. So, the adhesion of the furan molecule onto the surface of BNNT was consistent with the chemical functionalization. Furthermore, the computed density of states indicated that the electronic features of the BNNT were adjusted with a partial chemical modification. Also, the functional energy raised by enhancing the electron donation property of the functional groups, which was due to the rise in the electrical conductance of BNNT in contrast with the pristine BNNT. Retaining the electronic features of BNNT and the increased solubility demonstrated that using furan to chemically modify BNNTs could be a useful method to purify them.